THE EFFECT OF SERVICE QUALITY AND CUSTOMER VALUE ON CUSTOMER SATISFACTION AT PT. BANK SYARIAH INDONESIA TBK KCP PEUDADA, BIREUEN DISTRICT - Azhari; Yusnidar; Raudhatinur; Khairul Umam (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Companies must have clear long-term goals. Companies must strive to generate as much profit as possible. A customer-oriented approach should be implemented more systematically to be more effective. Because the majority of Indonesia's population is Muslim, the Islamic banking market in Indonesia is very large. Most banks use an interest system, but Islamic banks use a profit-sharing system. The purpose of this study was to determine whether service quality and customer value affect customer satisfaction at PT. Bank Syariah Indonesia Tbk KCP Peudada, Bireuen Regency. The method in determining the number of samples used Cochran as many as 97 customers with the determination using purposive sampling. The results of the study said that service quality and customer value on Customer Satisfaction at PT. Bank Syariah Indonesia, Tbk KCP Peudada, Bireuen Regency is 62.3% and the remaining 37.7% is influenced by other variables. F count of 77.548 is greater than F table of 3.09 which means that together the independent variables have a significant effect on the dependent variable. Service Quality (X1) and Customer Value (X2) have a positive and significant impact on Customer Satisfaction at PT. Bank Syariah Indonesia, Tbk, Peudada Branch Office, Bireuen Regency. Conclusion: Service quality enhances relationships and provides the desired value to customers, with the goal of ensuring customer satisfaction during transactions. By introducing Sharia products to customers, we aim to enhance customer satisfaction during transactions and as a customer overall.